UPAYA PENGAWAS DALAM MENINGKATKAN KOMPETENSI GURU DALAM MENETAPKAN KRITERIA KETUNTASAN MINIMAL (KKM) MELALUI IN HOUSE TRANING SEKECAMATAN WONOAYU - Nur Hidayati (Madaris: Jurnal Guru Inovatif, 2022)
Human resource development can be pursued through improving the quality of education. Assessment is very important in achieving efforts to improve the quality of education. Assessment activities are able to provide constructive feedback for teachers and students. The assessment in the 2013 curriculum has the principle of using reference criteria. In the 2013 Curriculum assessment standards, every school educator is obliged to establish Minimum Completeness Criteria (KKM) for each subject. The objectives of this study are: 1) whether the In House Training activity can improve teacher competence in determining the minimum completeness criteria (KKM) for the assisted teachers in Wonoayu sub-district. 2) how the implementation of In House Training activities can improve the ability of teachers in determining minimum completeness criteria (KKM) for assisted teachers in Wonoayu sub-district. This school action research was carried out in 2 cycles, the stages were planning, acting, observing the results of the action and reflecting. The instruments used were interviews, observation and research questionnaires. Cycles I and II show an increase in the quality of teacher competence with the results: (a) formulating indicators of 90.4%, (b) determining complexity of 91.1%, (c) determining carrying capacity of 92.6%, (d) determining student intake 91 , 9%, (e) determine KKM for indicator 94.1%, (f) determine KKM KD 100, (g) determine KKM MP 100%. Based on the results of the study, it was concluded that there was an increase in teacher competence in determining minimum completeness criteria with an increase in the success rate of each assessment indicator. Keywords: Competence, KKM, In House Training